2006
DOI: 10.1016/j.mce.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin augments GnRH-stimulated LHβ gene expression by Egr-1

Abstract: Previous studies have shown that insulin augments GnRH-stimulated LH synthesis and release from primary gonadotrophs. In this study, regulation of LHβ gene expression by GnRH and insulin was examined in LβT2 cells. Endogenous LHβ mRNA is stimulated 2.4-fold by insulin alone, 2.6-fold by GnRH alone, and 4.7-fold by insulin together with GnRH. This effect of insulin, like GnRH, mapped to sequences −140 to +1 in the mouse LHβ gene. Insulin together with GnRH stimulates activity of an LHβ-reporter gene 7.1-fold; w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
2
31
0
2
Order By: Relevance
“…Our sensitivity analysis, excluding girls with transient thelarche, showed similar (17). Furthermore, insulin resistance increases the levels of hyperandrogenemia (14), which in combination may facilitate the GnRH pulsatile secretion and increase pituitary secretion (37) and androgen secretion at the ovarian theca cells (16). Additionally, in adults, insulin and IGF1 stimulate breast cell division (7,8); thus, they could be involved in breast development in early puberty (9).…”
Section: Resultsmentioning
confidence: 77%
“…Our sensitivity analysis, excluding girls with transient thelarche, showed similar (17). Furthermore, insulin resistance increases the levels of hyperandrogenemia (14), which in combination may facilitate the GnRH pulsatile secretion and increase pituitary secretion (37) and androgen secretion at the ovarian theca cells (16). Additionally, in adults, insulin and IGF1 stimulate breast cell division (7,8); thus, they could be involved in breast development in early puberty (9).…”
Section: Resultsmentioning
confidence: 77%
“…Phosphorylation of CBP via insulin results in dissociation of CBP from the CREB-CBP-TORC2 complex, and in gonadotrophs, it results in recruitment to the Lhb promoter and activation of Lhb gene expression. We and others have shown that insulin can increase GNRH-mediated Lhb expression and secretion with some evidence of a costimulatory effect of insulin and GNRH in L␤T2 cells via activation of AKT and extracellular signal-regulated kinase (ERK) (1,4,10,31,40). This suggests that energy-homeostatic information can be integrated at the level of the pituitary gland, possibly through CBP, to modulate reproductive function.…”
Section: Discussionmentioning
confidence: 92%
“…The Lhb promoter-luciferase reporter contains the Ϫ140 to ϩ1 fragment of the mouse Lhb gene promoter cloned into pA 3 Luc proximal to luciferase as previously described (4). The wild-type CBP and S436A mutant vectors were generated using the QuikChange site-directed mutagenesis kit (Stratagene) as previously described (56).…”
Section: Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include insulin and fatty acids (Buggs et al 2006, Garrel et al 2014, indicating a potential role in mediating the effects of nutritional status and possibly obesity on reproductive capacity (shown in Brothers et al (2010)). In addition, there is evidence that EGR1 mediates the effects of glucocorticoids/stress at the Lhb gene promoter (Breen et al 2012).…”
Section: Introductionmentioning
confidence: 99%